ANALISIS PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN AIR MINUM DALAM KEMASAN PADA CV BIO ITE SUI - Sipahutar, Mia Aprianita; Syofian, Syofian; Hidayati, Arifah (STMIK Pringsewu, 2024)
This study aims to determine the effect of marketing mix on the sales volume of bottled drinking water of CV Bio Ite Sui. The method used in this research is quantitative method with data collection techniques in the form of questionnaires, documentation and observation. The results of this study are 1) Based on the results of the t test between X1 (Product) on Y (Sales Volume) has a significant value of 0.003, therefore 0.003 ≤ 0.05, so there is a significant influence between Products on Sales Volume of bottled drinking water at CV Bio Karya Ite. And based on the results of the Determination Coefficient test between Variable X1 on Y. has a value of R Square value of 729, meaning that there is a strong influence between products on sales volume.2) Based on the results of the t test between Variable X2 (Price) on Y (Sales Volume) has a significant value of 0.000, therefore 0.000 ≤ 0.05, so there is a significant influence between price on Sales Volume of bottled drinking water at CV Bio Karya Ite, and based on the results of the Determination test of Variable X2 (Price) on Y (Sales Volume) has a value of R Square value of 813, which means that there is a very strong influence between price and sales volume.3) Based on the results of the t test between Variable X3 (Promotion) on Y (Sales Volume) has a significant value of 0.002, therefore 0.002 ≤ 0.05, so there is a significant influence between Promotion on Sales Volume of bottled drinking water at CV Bio Karya Ite. And based on the results of the determination test of Variable X3 (promotion) against Y (Sales Volume) has a value of R Square value of 561, which means that there is a strong enough influence between promotion on sales volume.4) Based on the results of the t test between Variable X4 (Place) against Y (Sales Volume) has a significant value of 0.000, therefore 0.000 ≤ 0.05, this means that X4 on Y has a significant influence so that there is a significant influence between Place on Sales Volume of bottled drinking water at CV Bio Karya Ite. And based on the results of the determination test, variable X4 (place) on Y (Sales Volume) has an R Square value of 775, which means that there is a strong influence between Promotion on Sales Volume. 5) Based on the results of the F test, the significant value is ≤ 0.05. From the table above, it can be seen that the significant value of the F test results between variables X1, X2, X3 and X4 (Product, Price, Promotion and Place) on Y (Sales Volume) has a significant value of 0.000, therefore 0.000 ≤ 0.05, this means that X1, X2, X3 and X4 on Y simultaneously have a significant effect. So that the results of the hypothesis in this study are that there is a significant influence between Product, Price, Promotion and Place on the sales volume of bottled drinking water CV Bio Karya Ite.